2021
DOI: 10.1111/hae.14168
|View full text |Cite
|
Sign up to set email alerts
|

Identified unmet needs and proposed solutions in mild‐to‐moderate haemophilia: A summary of opinions from a roundtable of haemophilia experts

Abstract: Introduction: The experiences of patients with mild-to-moderate haemophilia differ from those of patients with severe haemophilia or those without a bleeding disorder and include a challenging diagnosis and variability in bleeding symptoms and treatment needs. In addition, there is a significant lack of data on mild-to-moderate haemophilia, and many unmet needs remain to be identified and addressed in this group of patients. Methods: Challenges for these patients, including women with haemophilia, were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…Additional information on these ideas and others can be found in this supplement. 35 Many patients with mild-to-moderate haemophilia in both studies reported haemophilia-related pain and functional impairment.…”
Section: Discussionmentioning
confidence: 96%
“…Additional information on these ideas and others can be found in this supplement. 35 Many patients with mild-to-moderate haemophilia in both studies reported haemophilia-related pain and functional impairment.…”
Section: Discussionmentioning
confidence: 96%
“…Potential solutions to these challenges were improved diagnostic guidelines, enhanced educational materials for patients, additional studies and scientific publications, and revised transition guidelines. 22 The conclusions of each of these articles reinforce the need for further research on mild-to-moderate haemophilia in both men and women and underscore the necessity for additional resources for this patient population.…”
Section: Women With Haemophiliamentioning
confidence: 85%
“…Financial problems and several medical appointments are concerns for people with CBDs. 24 Specifically, people with CBDs have many medi-cal appointments that complicate accommodating a regular dental appointment with their dentists. For example, it has been reported that the prevalence of the joint bleeding are 33% and 47% in children and 42% and 60% in adult with hemophilia A and B, respectively.…”
Section: Discussionmentioning
confidence: 99%